Założenia rowkowe o charakterze funeralnym ze stanowiska Domasław 10/11/12 / Chrzanów 4, pow. wrocławski jako przejaw oddziaływań kulturowych - Anna Józefowska; Lidia Kamyszek; Leszek Żygadło (Przegląd Archeologiczny)
The most interesting feature discovered in Domasław’s burial ground is the ditched enclosures complex of a funeral character. The oldest complex with a ring trench was dated to the middle Bronze Age (HaA2). This custom reaches its apogee in the early Iron Age (HaC). A total of 26 chamber graves encircled by trenches, as well as another ditch without a burial probably also from this period, were discovered in the cemetery. At the end of the Early Iron Age, burial practices within the Domasław necropolis did not cease completely. The category of sepulchral features with a younger chronology should also include the rectangular, nearly quadrangular structures which appear in the La Tene period and even at a later phase using this burial ground. The Domasław burials with surrounding trenches have no analogies in the nearest regions. Excavated circular structures make the largest group of funeral ditches to the north of the Carpathian and Sudeten Mountains. The influence on the shaping of the burial rite’s material remains as recorded in the form of chamber graves which stand out for their construction and furnishing, might be also treated as an element of impact. The appearance of circular ditches within this province might be also treated as an element of southern (Hallstatt) impact. The circular ditches at this burial ground is the manifestation of these influences. The strong impact from the Hallstatt circle probably led to profound changes in the sphere of beliefs, ideas, and social stratification. The custom of surrounding graves with rectangular ditches recorded in enclaves of the La Tène culture in Poland is undoubtedly the effect of the arrival of Celtic people from the south to these areas.